2008
DOI: 10.1111/j.1551-2916.2008.02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Resistance of Fully Dense ZrB2 with SiC, TaB2, and TaSi2 Additives

Abstract: were pressureless-sintered and post-hot isostatic pressed to their theoretical densities. Oxidation resistances were studied by scanning thermogravimetry over the range 11501-15501C. SiC additions improved oxidation resistance over a broadening range of temperatures with increasing SiC content. Tantalum additions to ZrB 2 -B 4 C-SiC in the form of TaB 2 and/or TaSi 2 increased oxidation resistance over the entire evaluated spectrum of temperatures. TaSi 2 proved to be a more effective additive than TaB 2 . Sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(49 citation statements)
references
References 16 publications
4
43
0
2
Order By: Relevance
“…Peng and Speyer [34] (1150°C to 1550°C). The addition of Ta-containing compounds improved the oxidation resistance of the materials over the entire temperature range studied, but the TaSi 2 performed better than the TaB 2 presumably because of the ability to form larger amounts of protective silica-based liquid.…”
Section: Additivesmentioning
confidence: 99%
“…Peng and Speyer [34] (1150°C to 1550°C). The addition of Ta-containing compounds improved the oxidation resistance of the materials over the entire temperature range studied, but the TaSi 2 performed better than the TaB 2 presumably because of the ability to form larger amounts of protective silica-based liquid.…”
Section: Additivesmentioning
confidence: 99%
“…When HfB2 and ZrB2 are pressed with a silica former, typically 10-30%SiC [44], a protective layer of SiO2 is formed that persists up to 1,800°C [69]. Peng et al found the addition of TaSi2 improved oxidation resistance up to 1,550°C due to the formation of a denser SiO2 layer which inhibits the inward diffusion of oxygen [70]. Zhang et al found the oxidation resistance could be improved to 2,400°C through the addition of lanthanum hexaboride (LaB6).…”
Section: Figure 27 the Specific Yield Strength Of Some High Temperamentioning
confidence: 99%
“…These features are attractive for extremely high temperature applications, such as next generation aerospace structures [5,6]. Usually, SiC particles are added into ZrB 2 to increase sinterability [2,7,8], oxidation resistance [8,10,11] and thermal conductivity [4,8,12,13]. One poor property of SiC particle-dispersed ZrB 2 matrix composites (hereafter denotes as SiC/ZrB 2 ) is its low fracture toughness.…”
Section: Introductionmentioning
confidence: 99%